State of the Art of Ethnic Entrepreneurship on Student: Bibliometrics Study - Mustain, Muhammad; Purnomo, Margo; Herawaty, Tetty (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Ethnic Entrepreneurship for college students presents an opportunity to build a business connected to their culture but also faces challenges such as access to capital and stereotypes. The main purpose of this article is to direct researchers in creating a theoretical framework and guide researchers who are new to ethnic entrepreneurship research among university students so that they know which journals and authors to consult when studying this phenomenon. To do so, this study used the Scopus database to determine the research fields with the most research results, the countries that have conducted the most ethnic entrepreneurship research, the journals that published the most research, and the most cited documents.